Концептуальні засади формування моделі інклюзивного управління ресурсним потенціалом суб’єктів агробізнесу - Степаненко, С. В. (Економічний простір, 2022)
Стаття присвячена обґрунтуванню концептуальних засад формування моделі інклюзивного управління ресурсним потенціалом суб’єктів агробізнесу. Запропоновано контурний базис змістовних ознак інклюзивних моделей розвитку бізнесу у аграрній сфері. Окреслено набір інструментів, які допомагають суб’єктам аграрного бізнесу набувати та реалізовувати переваги, пов’язані із включенням в інклюзивний бізнес-процес. Інструментами є соціально орієнтова-ний маркетинг, бізнес-операції, що мають інклюзивний характер, інклюзивні інновації як інновація будь-яких сучасних перетворень, фінансово-інвестиційні ресурси аграрного сектору, партнерські відносини, які складаються в мікросередовищі інклюзивного агробізнесу. Визначено та обґрунтовано етапи формування інклюзивної моделі раціонального управління ресурсним потенціалом бізнес-суб’єктів аграрної сфери. Розроблено концептуальну модель інклюзивного управління ресурсним потенціалом суб’єктів агробізнесу. The article is devoted to the substantiation of the conceptual foundations of the formation of a model of inclusive management of the resource potential of agribusiness entities. A contour base of meaningful features of inclusive models of business development in the agrarian sphere is proposed. A set of tools is outlined that help agrarian business entities acquire and realize the benefits associated with inclusion in the inclusive business process. The tools are socially oriented marketing, business operations that are inclusive in nature, inclusive innovations as the innovation of any modern transformations, financial and investment resources of the agricultural sector, partnership relations that develop in the microenvironment of inclusive agribusiness. The stages of the formation of an inclusive model of rational management of the resource potential of business entities in the agrarian sphere are defined and substantiated. The stages of formation of an inclusive model of the use of resource potential include: definition of strategy and specification of goals of a commercial and social nature; assessment of the factors of the business environment of the model and the system of motivators for its participants; involvement of participants in a mutually beneficial partnership; creation of an organizational and economic management mechanism for the use of resource potential; joining the informational online platforms of resources; determination of the final financial result of the participants' work within the inclusive model; formation of financial potential for solving non-commercial goals and goals for the development of rural areas; creating additional value and increasing the degree of participation of the agricultural sector in the social value chain; assessment of the cumulative effect of the functioning of the inclusive model; substantiation of directions and tools for improving the effectiveness of the functioning of the inclusive model. A conceptual model of inclusive management of the resource potential of agribusiness entities has been developed. The key factor in the implementation of the inclusive model is taking into account the factors of the internal and external business environment of agricultural entities, and the central element of the inclusive model of managing the resource potential of agrarian business entities is a matrix that combines basic tools and methods of using agricultural resources.
Conceptual principles of forming the model of inclusive management of the resource potential of agribusiness subjects
Keywords: концепція; модель управління; інклюзивна економіка; ресурсний потенціал; інструменти; суб’єкти агробізнесу; concept; management model; inclusive economy; resource potential; tools; agribusiness subjects